Pengaruh Gengsi, Diskon, dan Literasi Keuangan Terhadap Perilaku Konsumerisme Generasi Z di Kalangan Mahasiswa Manajemen - Khairani Marpaung; Tri Inda Fadhila Rahma (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
The research objectives were to determine the effect of prestige on consumerism behavior of generation Z in management students, to determine the effect of discounts on consumer behavior of generation Z on management students, to determine the effect of financial literacy on consumer behavior of generation Z among management student. This type of research is quantitative with a descriptive approach. The research sample used the probability sampling method with the results of 278 student respondents. The data analysis technique used path coefficients and smartPLS bootstrapping 3. Based on the results of the analysis, it is known that prestige, discounts, and financial literacy influence the consumer behavior of generation Z in among management students. Therefore, prestige, discounts, and financial literacy can increase generation Z consumer behavior among management students. Seeing the results of this study illustrating students who deepening economic-related science can also be affected and falling in the cycle of cultural cyrocermism and indicate that this consumerism behavior is still attached to generation Z. The future researchers hopes as a student or I can handle the tendency to behave consuming excessively.